2010
DOI: 10.1186/ar3215
|View full text |Cite
|
Sign up to set email alerts
|

Human articular chondrocytes express ChemR23 and chemerin; ChemR23 promotes inflammatory signalling upon binding the ligand chemerin21-157

Abstract: IntroductionChemerin is a chemotactic peptide which directs leukocytes expressing the chemokine-like receptor ChemR23 towards sites of inflammation. ChemR23 is a G protein-coupled receptor which binds several different ligands, and it is also expressed by other cell types such as adipocytes. In addition to chemotaxis, recent reports suggest that ChemR23 is capable of mediating either inflammatory or anti-inflammatory effects, depending on the type of ligand it binds. In the present study, we aimed to clarify w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
110
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 38 publications
(42 reference statements)
4
110
1
Order By: Relevance
“…In contrast, we and others (14) show that ChemR23 mRNA levels increase in human monocytes and macrophages after stimulation with LPS or the inflammatory cytokines TNF-a and IFN-g, suggesting that there are differences between mouse and human in the regulation and eventual function of ChemR23. This notion would be supported by the fact that chemerin has ChemR23-dependent antiinflammatory and protective effects in some mouse models of inflammation (39,40), whereas in humans, chemerin was shown to induce inflammatory signaling in chondrocytes (41) and increased chemerin concentrations were associated with pathologies connected with chronic and systemic inflammation (19,21,(42)(43)(44). The differential expression pattern of ChemR23 on stimulated macrophages and the possible opposite effect of chemerin on inflammation between mouse and human may indicate that the role of ChemR23 signaling differs between the two species.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, we and others (14) show that ChemR23 mRNA levels increase in human monocytes and macrophages after stimulation with LPS or the inflammatory cytokines TNF-a and IFN-g, suggesting that there are differences between mouse and human in the regulation and eventual function of ChemR23. This notion would be supported by the fact that chemerin has ChemR23-dependent antiinflammatory and protective effects in some mouse models of inflammation (39,40), whereas in humans, chemerin was shown to induce inflammatory signaling in chondrocytes (41) and increased chemerin concentrations were associated with pathologies connected with chronic and systemic inflammation (19,21,(42)(43)(44). The differential expression pattern of ChemR23 on stimulated macrophages and the possible opposite effect of chemerin on inflammation between mouse and human may indicate that the role of ChemR23 signaling differs between the two species.…”
Section: Discussionmentioning
confidence: 98%
“…Here, chemerin stimulates angiogenesis (Bozaoglu et al, 2010;Kaur et al, 2010), matrix metalloproteinase (MMP) activity and cell survival (Kaur et al, 2010). In chondrocytes which also express CMKLR1 chemerin induces production of proinflammatory cytokines and MMP13 (Berg et al, 2010). However, the effect of chemerin on hepatocytes has not been studied so far.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effects of chemerin treatment on AKT phosphorylation: chemerin increases phosphorylation of Ser473 in both human umbilical vein endothelial cells, leading to the activation of endothelial nitric oxide synthase and increased nitric oxide [21,22], and in human articular chondrocytes, promoting inflammatory signalling [23]; on the other hand, it decreases phosphorylation at Thr308 in both human skeletal muscle cells (in which Ser473 phosphorylation is also decreased) [24,25] and, in vivo, in mouse skeletal muscle [26], leading in both cases to insulin resistance. Zhang et al (2014) have recently found that chemerin diminished the glucose uptake by rat cardiomyocytes, and suggested that this effect could be mediated by a negative influence of chemerin on AKT phosphorylation [59], other authors have found that in skeletal muscle of mice chemerin treatment decreased the insulin-stimulated AKT phosphorylation, produced alterations in the mitochondrial function and increased oxidative stress, with implications in the regulation of insulin resistance [57].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%